2018
DOI: 10.15446/dyna.v85n204.67961
|View full text |Cite
|
Sign up to set email alerts
|

Development of an information system for teleoperated physical rehab care service via Internet. Pilot case: patients with mild knee injury who live in geographically vulnerable zones

Abstract: In recent years, new technologies have been implemented for treating and rehabilitating of diseases, such as distance medicine, known as telemedicine. With the participation of an interdisciplinary group of researchers from Universidad del Valle and health professionals, a pilot project was established to test a teleoperated care system with a prototype designed for the rehabilitation of patients with mild knee injury in the of public health network ESE Ladera in Cali, Colombia, to provide physical rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Other studies [9] concluded that isokinetic workouts were the best at increasing isokinetic strength, an important variable to supervise under a rehabilitation process by healthcare personnel. In this sense, it is advisable to integrate these technological advances with information technologies to improve the implementation of telemedicine programs in physical rehabilitation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies [9] concluded that isokinetic workouts were the best at increasing isokinetic strength, an important variable to supervise under a rehabilitation process by healthcare personnel. In this sense, it is advisable to integrate these technological advances with information technologies to improve the implementation of telemedicine programs in physical rehabilitation [10,11].…”
Section: Introductionmentioning
confidence: 99%